DISTRIBUTION AND SIMILARITY COEFFICIENTS OF FERNS AND ALLIES IN THREATENED WETLANDS OF SOUTHERN AKWA IBOM STATE-NIGERIA - Mbong, Emem O.; Chukwudi, Peter; Konyeme, Thelma E. (FUDMA JOURNAL OF SCIENCES, 2025)
This study assessed the composition, distribution, and ecological similarity of ferns and fern allies across seven threatened wetlands within Eket Local Government Area, Akwa Ibom State, Nigeria using systematic sampling method. Visual inspection, taxa identification and direct counting procedure were employed to evaluate wetland vegetation. The results revealed 17 species from fifteen genera, representing 12 families. Species encountered included Asplenium sandersonii, Cyclosorus interruptus, Diplazium esculentum, Gleichinia linearis, Lycopodium clavatum, Lygodium microphyllum, Lygodium smithianum, Microgramma owariensis, Nephrolepsis bisserata, Oleandra distenta, Pityrogramma calomelanos, Platycerium stemaria, Pteridium aquilinum, Pteris sp., Phymatosorus scolopendria, and Sellaginella krausiana. Etebi and Ikot Udota wetlands each, had 10 species, whereas Atabong and Idim afia wetlands each, had 4 and 2 species, respectively. Cyclosorus interuptus and Nephrolepsis bisserata were common to all studied locations. Sorenson and Jaccard similarity indices revealed floristic overlap between some sites, with Ikot Usoekong and Ataobong (0.800 and 0.6667, respectively) being the most similar, and Etebi and Ikot Udota (0.3177 and 0.1875, respectively) the most dissimilar. Cluster analysis grouped sites into three major clusters, corresponding with disturbance gradients (roadside versus interior wetlands). Species diversity was notably higher in less disturbed wetlands, indicating that anthropogenic influence was a strong determinant of species composition. The findings highlight the ecological importance of ferns in wetland systems and their potential role in conservation monitoring. This study provides vital baseline data for future ecological assessments, conservation planning, and habitat restoration strategies targeting wetlands and their cryptogamic flora in Southern Nigeria.